Landfill site restoration and revegetation - Norafiza Awang (School of Environmental Engineering, University Malaysia Perlis, 2012)
This study focuses on restoration and revegetation process at Kuala Perlis and Padang Siding landfill sites. From both landfills, the characteristics of leachate before and after restoration process will be determined. The characteristics that will be measured include BOD, COD, ammoniacal nitrogen, and heavy metals (Zn and Cr6+). These samples were collected from four different points of leachate collection pipes, which are Environmental Site Assessment (ESA), 2 points of manholes and Perlis River for Kuala Perlis landfill and leachate pond at Padang Siding landfill to checked either the effluent from landfill is follow Standard B in Environmental Quality (Sewage and Industrial Effluents) Regulations, 1979 or not. The percentage of soil compound is measured by using XRF and Atomic Absorption Spectrophotometer (AAS) to determine the concentrations of heavy metal uptakes by native plant. Soil samples were taking from four different areas in Kuala Perlis landfill site which are top soil, soil outside the boundary of landfill, soil with waste and embankment soil. Native plant samples were taken from four different parts of plant: root, stem, leaf and flower. The critical aspects in landfill site restoration is characterized by a detailed reconstruction of the project site topography, site geomorphology, soil types conductive to the native plants of the area, surface hydrology and native plant species, their diversity and distribution. In the construction, it consists of site cleaning process, which includes the process of cut and fills waste, preparation of soil foundation layer and embankment process. While the efficiency of restoration process in Kuala Perlis landfills considering a successful restoration of convincing the public that landfill are an acceptable means of waste disposal. Selection of an appropriate site, good operational practice and site design are other important elements. Restoration and aftercare are both essential steps in the process of waste disposal, and must be considered at all stages of the life of the site if landfilling is to be managed in a way that minimizes environmental impacts.